Pendidikan Anti Konsumerisme dalam Novel Napoli: Ketika Jatuh di Pelukanmu Karya Riskaninda Maharani (Kajian Sosiologi Sastra) - Winda Dwi Hudhana; Nur Ariyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: This literary sociology study has the goal of describing the consumer culture contained in novel â€œNapoli: Ketika Jatuh di Pelukanmu (When Falling in your arms) by Riskaninda Maharani. The object of this study are the kind of object of consumption in the novel â€œNapoli: Ketika Jatuh di Pelukanmuâ€ Sociology approach of the literature by analyzing literary texts relating to consumer culture in the novel. Consumption of different types of objects such as architecture, fashion, food and beverage and body ideals that made a lot of consumer culture in the novel. Keywords: Consumer Culture, Novel, Literature Sociology